Global distribution of Echinococcus granulosus genotypes in domestic and wild canids: a systematic review and meta-analysis. Issue 9 (20th August 2022) - Shams, Morteza; Khazaei, Sasan; Naserifar, Razi; Shariatzadeh, Seyyed Ali; Anvari, Davood; Montazeri, Fattaneh; Pirestani, Majid; Majidiani, Hamidreza
Abstract: Abstract: The current systematic review and meta-analysis demonstrate the genotypic distribution of canine echinococcosis worldwide. Studies published from the inception until 21 May 2021 were screened, relevant articles were selected and the random-effect model was used to draw forest plots with 95% confidence intervals (CIs). Totally, 44 articles were included, mostly examined dogs (37 records), followed by wolf (8 records), jackal (7 records), fox (3 records), pump fox (3 records) and coyote (1 record). Echinococcus granulosus sensu stricto (G1–G3) and G6/7 cluster of Echinococcus canadensis were the most common genotypes among canids. Most studies were conducted in Asia and Europe with 17 and 15 datasets, respectively. Exclusively, Iran possessed the highest number of studies (10 records). Meta-analysis showed that the pooled molecular prevalence of echinococcosis was 33.82% (95% CI 24.50–43.83%). Also, the highest and lowest prevalence of canine echinococcosis was calculated for South America (66.03%; 95% CI 25.67–95.85%) and Europe (19.01%; 95% CI 9.95–30.16%). Additionally, there were statistically significant differences between the global prevalence of echinococcosis in canines and publication year, continent, country, sample type, host and molecular test. These findings will elevate our knowledge on the poorly known canine echinococcosis worldwide.